The effects of fansubs on EFL education for Translation and Interpreting students: an empirical approach - Alejandro Bolaños García-Escribano (JoSTrans: The Journal of Specialised Translation)
This article reports on an empirical experiment conducted with Translation and Interpreting undergraduate students to gauge the effects of fansubbing on learning English as a foreign language (EFL). Experience has shown that young Spanish-speaking undergraduate students tend to watch free TV programmes online, and these programmes may be fansubbed in Spanish, which means that fansubbed videos are acting as a linguistic model to many students of English as a foreign language. This study aims to ascertain the potential benefits, as well as the main drawbacks, of using fansubbed products for foreign language learning purposes in translator training. This research targeted students in their second year of studies whose participation was twofold: firstly, they were invited to complete an online survey to collect data on their opinions about subtitling and fansubbing; secondly, the students were exposed to two short clips, one professionally subtitled and one fansubbed. This was followed by a blind experiment including a questionnaire with an assessment test and more personal questions. The survey was successfully completed by 46 students and throws light on their preferences for audiovisual consumption when learning a foreign language. The blind experiment was successfully completed by 59 students and provides evidence of the effects fansubbing may have on foreign language education.